HPV-DNA test access based on self-collection of vaginal samples from women living with HIV/AIDS: pilot implementation in Brazil - Gaspar, Pamela; de Melo Machado, Hanalydia; Bazzo, Maria Luiza; Scherer, Aline; Colusso, Álvaro Luis; Álvares Travassos, Ana Gabriela; Arakaki-Sanchez, Denise; Baia-da-Silva, Djane Clarys; Campos de Oliveira, Eduardo; Ribeiro Zago, Isabella; et al. (Brazilian Journal of Sexually Transmitted Diseases, 2024)
Introduction: Women living with HIV/AIDS have a higher frequency of anogenital neoplasms resulting from human papillomavirus (HPV) infection. The World Health Organization recommends that cervical cancer screening uses molecular tests that amplify viral genetic material, such as HPV-DNA. In addition to collection by health professionals, self-collection of vaginal samples is a useful tool for expanding access to testing. Objective: To describe the results of the pilot study that evaluated the acceptability of self-collection of vaginal samples and the applicability of offering HPV-DNA tests with self-collection of vaginal samples for women living with HIV/AIDS in Brazil. Methods: Descriptive cross-sectional study involving women living with HIV/AIDS treated in eight HIV-specialty healthcare facilities distributed in all regions of the country from May 2021 to May 2022 and a central laboratory. Vaginal self-collection was offered, and participants were interviewed about sociodemographic data and impressions of self-collection. Results: In total, 1,919 women living with HIV/AIDS with an average age of 45 years participated in the study. Some type of HPV was detected in 66% (1,267) of cases. The majority (71.9%) said they preferred self-collection to sample collection by health care professionals. Only 53.8% of participants underwent cytology at the appropriate frequency, as recommended by the protocol. Conclusion: The results may support the implementation of molecular biology tests to detect HPV in women living with HIV/AIDS, including the possibility of vaginal self-collection, promoting increased access to cervical cancer screening. Keywords: HIV seropositivity. Human papillomavirus viruses. Mass screening. Uterine cervical neoplasms. Health services.